2020
DOI: 10.2147/opth.s236637
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Evolving Treatment of Diabetic Retinopathy</p>

Abstract: Purpose: To review the current therapeutic options for the management of diabetic retinopathy (DR) and diabetic macular edema (DME) and examine the evidence for integration of laser and pharmacotherapy. Methods: A review of the PubMed database was performed using the search terms diabetic retinopathy, diabetic macular edema, neovascularization, laser photocoagulation, intravitreal injection, vascular endothelial growth factor (VEGF), vitrectomy, pars plana vitreous surgery, antiangiogenic therapy. With additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
134
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(147 citation statements)
references
References 285 publications
(229 reference statements)
0
134
0
13
Order By: Relevance
“…The clinical presentation of nvAMD and diabetic eye disease is characterised by a spectrum of phenotypes, and although the anti-VEGF therapeutics are generally highly effective the heterogeneity of these conditions is accompanied by a variable response to treatment. [22][23][24] Attempts to generate improved therapeutics that capture poor-and non-responders can be broadly divided into two categories, one being the development of alternative and longer-acting anti-VEGFs, while other efforts have focused on alternative targets such as Ang2 and PDGF. 25 It was a search for novel regulators of pathological angiogenesis that led us, through transcriptomic analysis of a number of rodent models of retinal vascular disease, to the discovery of LRG1.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation of nvAMD and diabetic eye disease is characterised by a spectrum of phenotypes, and although the anti-VEGF therapeutics are generally highly effective the heterogeneity of these conditions is accompanied by a variable response to treatment. [22][23][24] Attempts to generate improved therapeutics that capture poor-and non-responders can be broadly divided into two categories, one being the development of alternative and longer-acting anti-VEGFs, while other efforts have focused on alternative targets such as Ang2 and PDGF. 25 It was a search for novel regulators of pathological angiogenesis that led us, through transcriptomic analysis of a number of rodent models of retinal vascular disease, to the discovery of LRG1.…”
Section: Discussionmentioning
confidence: 99%
“…Dramatic advances in the diagnosis and treatments of DR have been made [ 14 ]. To date, treatments for DR are laser photocoagulation, topical injection of corticosteroids, intravitreal injection of anti-vascular endothelial growth factor (VEGF) agents, and vitreoretinal surgery [ 15 ]. These treatments are applicable only at the late stages of DR and may cause significant side effects [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further intensification of treatment to maintain HbA1c below 6% with the modalities available today poses severe risks of hypoglycemia in T2DM patients with increased mortality [67]. In this perspective, local and systemic treatments with biological compounds as well as with the somatostatin analog octreotide [68][69][70] are promising additional tools. In 2000, Aksoy et al found an inverse relationship between presence and severity of DR, and VD concentrations, being the lowest in proliferative DR and the highest in diabetic patients without DR [71].…”
Section: Diabetic Retinopathymentioning
confidence: 99%